2013
DOI: 10.1080/00918369.2013.773815
|View full text |Cite
|
Sign up to set email alerts
|

LGB Identity Among Young Chinese: The Influence of Traditional Culture

Abstract: Based on the social construction perspective, this research aims to investigate how traditional cultural values may affect the way individuals interpret and negotiate with their minority sexual identity. Using an online survey questionnaire with a student sample of 149 Chinese lesbian, gay, and bisexual (LGB) individuals, 2 elements of traditional Chinese culture were found to be associated with negative LGB identity among Chinese LGB students-namely, perceived parental attitudes toward marriage and participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 33 publications
1
89
0
Order By: Relevance
“…One-third of LGB youths have reported experiencing verbal abuse from their families, and 1/4 have reported being physically bullied by their peers. That is, the prevalence of victims of violence of LGB youths is similar in Asian countries when compared to western countries [8, 22]. It has been suggested that LGB youths hide their concerns about sexual orientation, feelings of isolation or helplessness, and stigmatization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One-third of LGB youths have reported experiencing verbal abuse from their families, and 1/4 have reported being physically bullied by their peers. That is, the prevalence of victims of violence of LGB youths is similar in Asian countries when compared to western countries [8, 22]. It has been suggested that LGB youths hide their concerns about sexual orientation, feelings of isolation or helplessness, and stigmatization.…”
Section: Discussionmentioning
confidence: 99%
“…A social atmosphere of condemning and forbidding homosexuality has been established, leading to a stigmatization of homosexuality as a pathological disorder. In the current study, LGB youths living in Asian cities received little support from their friends, and commonly experienced teasing or were treated unfairly [22, 26]. One can imagine the difficulties that Korean LGBs may experience with such social prejudice against homosexuality.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of some significant social change, previous research indicates that the nature of the relationship between the authorities and LGBT people in China remains problematic (Bartram ; Hu and Wang ; Wei ). Research by Tu and Lee () found LGBT people across China generally tend to conceal their sexuality due to the lack of legal protection, as well as family and social pressure, and a combination of these factors keeps most Chinese homosexual people in the closet.…”
Section: Introductionmentioning
confidence: 99%
“…Hu and Wang () argue that the problems underpinning hidden sexual identities stem from cultural values which fundamentally shape how Chinese LGBT people perceive themselves. Research identifying individual and social factors that support or obstruct open and hidden sexual identities is severely lacking in China where LGBT people are stigmatized and marginalized (Yu, Xiao and Xiang ), and where the dynamic interaction between culture and identity is perceived by many to be relatively fixed in social terms (Hong et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Some WSW postpone coming out to their families due to social and familial pressures and expectations of heterosexuality. [35][36][37][38][39][40] Some feel pressured to marry men, while others hide their sexual identity due to fear of social exclusion, discrimination, and violence. [41][42][43][44] Anti-gay laws negatively affect homosexuals and put them under distress.…”
Section: Other Findingsmentioning
confidence: 99%